Dragonflies in Bawean Island Nature Reserve, Indonesia - Rohman, Abdu; Sulistyono, Setyo; Nuryati, Wahyu; Arifandy, Ahmad; Setiyanto, Aris (Borneo Journal of Resource Science and Technology, 2020)
Bawaean Island is known for its endemic Bawa deer and other vertebrate species of mammals, avians and reptiles. However, little is known about the invertebrates, especially the Odonata (dragonflies) group. The aim of this study was to examine the variety of dragonflies on the Bawaean Island. The observation method was employed for data collection while the Shannon-Weinner Diversity Index was used for data analysis. A total of 23 dragonflies’ species consisting of four families were collected throughout the study. These include Coegnagrionidae (6 species), Libellulidae (13 species), Platycnemididae (2 species) and Aeshnidae (1 species). Ischnura senegalensis is the most dominant species. The diversity index (absolute H index) shows a moderate level of diversity in Bawean Island, with a value of 1,007.